Effects of proprioceptive exercise for knee osteoarthritis: a systematic review and meta-analysis - Lin, Yaoyu; Yu, Debiao; Chen, Xiaoting; Chen, Peng; Chen, Nan; Shao, Bin; Lin, Qiuxiang; Wu, Fuchun (Frontiers in Rehabilitation Sciences, 2025)
Background and objectiveDespite the extensive utilization of proprioceptive exercise in the management of knee osteoarthritis (KOA), the therapeutic efficacy of this approach remains inconclusive. The present study sought to systematically evaluate the effects of proprioceptive exercise on symptoms and functional outcomes in patients with KOA, with a particular focus on balance performance.MethodsFollowing PRISMA guidelines, a comprehensive search was conducted across six electronic databases from the establishment of the database to January 21, 2025. The inclusion criteria were randomized controlled trials investigating proprioceptive exercise interventions for KOA. The primary outcome measures encompassed balance function assessment (Timed Up and Go test), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) total score and its pain, stiffness, and function subscales, and pain intensity (Numerical Rating Scale and Visual Analog Scale). Subgroup analyses were stratified by intervention duration (≤8 weeks vs. >8 weeks).ResultsA comprehensive analysis of 22 randomized controlled trials revealed that proprioceptive exercise significantly improved performance of the Timed Up and Go test [MD = 1.53, 95% CI (1.09, 1.97), I2 = 0%, P < 0.00001]. Additionally, a significant improvement in WOMAC-total scores was observed [MD = 3.37, 95% CI (1.58, 5.16), I2 = 44%, P = 0.0002]. However, individual WOMAC subscales for pain (P = 0.11, I2 = 85%), stiffness (P = 0.97, I2 = 0%), and function (P = 0.16, I2 = 86%) showed no significant improvements. For pain assessment, Numerical Rating Scale scores showed a significant improvement [MD = 0.85, 95% CI (0.56, 1.15), I2 = 46%, P < 0.00001]. Notably, Visual Analog Scale scores exhibited a significant reduction, but only in the short-term intervention subgroup (≤8 weeks) [MD = 0.27, 95% CI (0.11, 0.42), I2 = 0%, P = 0.0008], whereas longer interventions (>8 weeks) showed no significant benefit [MD = −0.49, 95% CI (−1.10, 0.11), I2 = 0%, P = 0.11].ConclusionBased on low-certainty evidence, proprioceptive exercise has been demonstrated to be efficacious in improving balance function and overall clinical status in patients with KOA. Optimal benefits have been observed during short-term intervention periods.